Troops, Trolls and Troublemakers: A Global Inventory of Organized Social Media Manipulation - Bradshaw, S; Howard, P (Oxford Internet Institute, 2017)
Cyber troops are government, military or political party teams committed to manipulating public opinion over social media. In this working paper, we report on specific organizations created, often with public money, to help define and manage what is in the best interest of the public. We compare such organizations across 28 countries, and inventory them according to the kinds of messages, valences and communication strategies used. We catalogue their organizational forms and evaluate their capacities in terms of budgets and staffing. This working paper summarizes the findings of the first comprehensive inventory of the major organizations behind social media manipulation. We find that cyber troops are a pervasive and global phenomenon. Many different countries employ significant numbers of people and resources to manage and manipulate public opinion online, sometimes targeting domestic audiences and sometimes targeting foreign publics. ·The earliest reports of organized social media manipulation emerged in 2010, and by 2017 there are details on such organizations in 28 countries. ·Looking across the 28 countries, every authoritarian regime has social media campaigns targeting their own populations, while only a few of them target foreign publics. In contrast, almost every democracy in this sample has organized social media campaigns that target foreign publics, while political-party-supported campaigns target domestic voters. ·Authoritarian regimes are not the only or even the best at organized social media manipulation. The earliest reports of government involvement in nudging public opinion involve democracies, and new innovations in political communication technologies often come from political parties and arise during high-profile elections. ·Over time, the primary mode for organizing cyber troops has gone from involving military units that experiment with manipulating public opinion over social media networks to strategic communication firms that take contracts from governments for social media campaigns.